Morbimortality and malignancy in patients treated with the Sistrunk procedure technique for the treatment of thyroglossal duct cyst in UMAE hospital de Especialidades Dr. Antonio Fraga Mouret Centro Médico Nacional La Raza - Saucedo, Daniel; Arenas, Jésus (International Surgery Journal, 2023)
Background: Describes the morbidity and malignancy in patients treated with the Sistrunk procedure technique for the treatment of thyroglossal cyst from 2017 to 202 in UMAE specialty hospital "Dr Antonio Fraga Mouret” CMN La Raza. Methods: Retrospective, cross-sectional, observational, descriptive and analytical study. The study population consisted of patients older than 18 years of age with a diagnosis of thyroglossal duct cyst, treated with the Sistrunk procedure technique between January 2017 and July 2022. Results: The 31 patients were included. 21 of the female gender and 10 of the female gender. The average age was 41.29 years. The age range with the largest number of patients was 35-50 years. The most frequent presenting symptom was painless cervical enlargement. Comorbidities occurred in 48.37% of the patients. The average size was 3.64×2.59 cm. The most frequent location was the infrahyoid (51.61%). Morbidity was 9.67%, 3 patients presented immediate postoperative complications, of which 2 (6.45%) patients presented bleeding that required urgent surgical reoperation with adequate resolution and 1 (3.23%) patient presented solid dysphagia that was resolved with conservative treatment. No intraoperative or late postoperative complications were recorded. Mortality was nil. The average number of days of hospital stay was 3.06 days. The presence of malignancy was null. Conclusions: Morbidity in this series of patients was 9.67%. Mortality and presence of malignancy were null.